THE DIFFERENCES IN STRESS SCORES AFTER BEING GIVEN MUROTTAL THERAPY QS AL-ANBIYA 83 – 112 IN HYPERTENSION SUFFERERS - Indarti, Erni Tri (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
The increasing incidence of hypertension with various accompanying complications is caused by several factors, including excessive sympathetic nerve activity, obesity, food, unhealthy lifestyles, hereditary factors, and stress. The many impacts caused by stress that are not handled immediately require someone to be able to carry out stress management. Non-pharmacological therapy through stress management in cases of hypertension has been widely developed and applied, such as providing yoga relaxation therapy, massage therapy, meditation, and murottal therapy. Murottal therapy has a relaxing effect and improves body cells and creates a sense of comfort in the soul, thereby reducing stress. The purpose of this study was to determine the The effect of murottal QS Al-Anbiya 83–112 on stress levels in hypertension sufferers. The study used a pre-experimental design with a One-group pre-post test design which was carried out on 4th-10 th 2023. The population of this research is 30 of patient with hypertention was spreading at Nglaban Hamlet, Nglaban Village, Loceret District, Nganjuk Regency. A sample of 22 respondents with purposive sampling technique. Measurement of stress levels before and after being given murottal QS Al-Anbiya 83–112 with Depression Anxiety Stress Scales (DASS 42). Provision of Murottal QS Al-Anbiya 83–112 for 9 minutes once a day for seven days. Data analysis used the Wilcoxon sign rank statistical test. The results of the Wilcoxon sign rank statistical test showed P value = 0.000 <α = 0.05 so that there was an effect of murottal QS Al-Anbiya 83–112 on stress levels in hypertension sufferers. Murottal QS Al-Anbiya 83–112 can be applied as an alternative solution in overcoming the stress levels of hypertension sufferers.